Phipps, J. B. 1997. Monograph of Northern Mexican Crataegus (Rosaceae, Subfam. Maloideae). Sida, Botanical Miscellany No. 15. Botanical Research Institute of Texas, Inc. 94 pp - Madrigal Sánchez, Xavier (Instituto de Ecología, A.C., 2022)
Reseña de libro